Decision Support System For Seed Aid Recipients Using The Combined Compromise Solution Method (Case Study: Among Tani Farmer Group) - Anis Putri Purwanti; Andi Iwan Nurhidayat; Dodik Arwin Dermawan; Rosita (Universitas Negeri Surabaya, 2026)
The distribution of seed assistance in the Among Tani Farmer Group, Magetan, has traditionally relied on manual assessment and subjective judgment, increasing the risk of inconsistent recipient selection. This study develops a web-based Decision Support System (DSS) that applies the Combined Compromise Solution (CoCoSo) method to prioritize 148 farmer candidates based on five evaluation criteria: economic condition, cultivated land area, land readiness, previous aid history, and land tenure status. Primary data were collected through interviews and field observations, then converted into standardized 1–5 ratings using predefined assessment rules established with the farmer group administrators before being processed through the CoCoSo algorithm. The system was implemented using Laravel 12 and MySQL to provide transparent and traceable ranking results. The proposed system generated a complete ranking of all candidates, supporting the prioritization of 100 farmers according to the available assistance quota, while the remaining 48 farmers were categorized as requiring further consideration. Computational verification against an independent Microsoft Excel implementation produced identical Ki values for all 148 alternatives, confirming the correctness of the CoCoSo implementation. Functional testing across 72 black-box test scenarios indicated that all system features operated as intended. In addition, a comparative analysis with the Simple Additive Weighting (SAW) method revealed notable differences in ranking outcomes, particularly among highly ranked alternatives, demonstrating the distinct aggregation characteristics of the CoCoSo method.